Global burden of colon and rectal cancer and attributable risk factors in 204 countries and territories from 1990 to 2021 - Xuyuan Zhang; Haoyu Fan; Sen Han; Ting Zhang; Yanxia Sun; Liuyang Yang; Wenliang Li (BMC Gastroenterology)
Abstract Objective Colon and rectal cancers (CRCs) are among the most common malignancies worldwide. While previous studies have examined the disease burden and risk factors of CRC at regional levels, they lack the granularity needed for country-specific policy development. Using updated data from the Global Burden of Disease (GBD) 2021 study, this research explores the national-level spatial distribution of CRC burdens linked to key risk factors and analyzes temporal trends in their contributions. The findings aim to support the formulation of precise public health policies to effectively reduce CRC incidence. Methods Based on data from the GBD study 2021, we examined CRC-related incidence, prevalence, mortality, disability-adjusted life years (DALYs), and associated risk factors. Age-standardized incidence rate (ASIR), age-standardized mortality rate (ASMR), and DALY rate (ASDR) were obtained and analyzed from 1990 to 2021. We used regression analysis and stratification across the four World Bank regions to assess geographical variations and the effect of economic development levels. We further assessed the contribution of various risk factors to CRC-related deaths and DALYs, while analyzing the distribution and temporal trends of the top three contributing risk factors. Results On a global scale, the ASDR for CRC declined from 357.33 per 100,000 in 1990 to 283.24 per 100,000 in 2021 (95% confidence interval [CI]: -0.82 to -0.64). In 2021, the regions classified by the World Bank as high income exhibited the highest ASDR in 2021, at 347.35 per 100,000, while the lower-middle-income regions reported the lowest ASDR, at 179.48 per 100,000. During this period, the global ASMR fell from 15.56 to 12.40 per 100,000, while the ASIR rose from 24.04 to 25.60 per 100,000. However, these trends were not consistent across different World Bank income regions. Key risk factors contributing to CRC included high red meat consumption, obesity, insufficient calcium intake, and alcohol consumption, with variations observed among the World Bank income groups. Conclusion Although the global burden of colorectal cancer (CRC) has declined from 1990 to 2021, particularly in high-income regions, the incidence rate continues to rise. The increase is more pronounced among individuals aged 50 years and older, who also bear a higher absolute incidence than younger populations. High red meat consumption, high body mass index (BMI), and low calcium intake remain the leading global risk factors for CRC. Effective weight management and the promotion of healthy lifestyles are essential strategies for reducing CRC risk across sexes, while smoking and alcohol control are particularly critical for alleviating the burden among males.